Strategi Manajemen Kepala Sekolah dalam Peningkatan Motivasi Belajar Siswa pada Masa Pandemi Covid-19 di SMA Negeri 1 Muaro Jambi - Suci Eka Nurhaslina (JMiE (Journal of Management in Education), 2023)
This study aims to describe the principal’s management in enhancing students’ learning motivation during the Covid-19 pandemic at SMA Negeri 1 Muaro Jambi. The research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The findings reveal that the shift from face-to-face instruction to online and limited offline learning created various challenges that affected students’ learning motivation. To address these challenges, the principal implemented strategic efforts by fostering collaboration among teachers, parents, and the school. This collaboration was crucial in ensuring the continuity of the learning process and achieving educational goals during the pandemic. This study highlights that effective principal management, particularly in building collaborative efforts, plays a vital role in maintaining students’ learning motivation in times of crisis. It further indicates that learning success during the pandemic was not only determined by students’ internal factors but also by the synergy between schools and families.